Desenvolvimento territorial no Rio Grande do Norte: uma identificação de clusters rurais - Vale, Fábio Freire Ribeiro do (2011)
The general objective of this study is the identification of rural spaces in Rio Grande do Norte through a territorial approach. It looks if there is spatial correlations between municipalities that influence and are influenced by the rural environment, allowing the identification of clusters. To accomplish this objective it`s used, in the methodology, the factor analysis of principal components to achieve the indicators of rurality and territorial development, that deal with four dimensions of analysis: environmental, political-institutional, economical and spatial. Moreover, to identify the spatial correlations structure between municipalities it used the Moran index to both rurality and territorial development, leading to clustering identification. The results show that the rurality is present in most of Rio Grande do Norte municipalities, except in cases like Mossoró, Pau dos Ferros, Caicó and Natal, where can be regional dynamic poles. It is also verified that the more rural municipalities tend to be less developed, according to the territorial development index, and have less correlations with neighboring municipalities